The effect of medications associated with drug-induced pancreatitis on pancreatic cancer risk: A nested case-control study of routine Scottish data. (April 2021) - McDowell, R.D.; Hughes, C.M.; Murchie, P.; Cardwell, C.R.
Highlights: Inflammation plays a role in pancreatic cancer. Many medicines are known to cause inflammation of the pancreas. We studied medicines with the strongest evidence for drug-induced pancreatitis. Little evidence of associations between these medicines and pancreatic cancer. Medicines associated with pancreatitis not associated with pancreatic cancer. Abstract: Background: Inflammation plays a role in pancreatic cancer. Many medications cause pancreatic inflammation, with some leading to a diagnosis of drug-induced pancreatitis (DIP), but few studies have examined these medications and pancreatic cancer risk. We therefore investigated the associations between pancreatic cancer risk and commonly-prescribed medicines for which there is strongest evidence of DIP. Methods: A nested case-control study was undertaken using the Primary Care Clinical Informatics Unit Research database containing general practice (GP) records from Scotland. Pancreatic cancer cases, diagnosed between 1999 and 2011, were identified and matched with up to five controls (based on age, gender, GP practice and date of registration). Medicines in the highest category of evidence for DIP, based on a recent systematic review, and used by more than 2 % of controls were identified. Odds ratios (OR) and 95 % confidence intervals (CI) for associations with pancreatic cancer were calculated using conditional logistic regression after adjusting for comorbidities. Results: There were 1, 069 cases and 4, 729 controls. Thirteen medicines in the highest category of evidence for DIP were investigated. There was little evidence of an association between any of these medications and pancreatic cancer risk apart from metronidazole (adjusted OR 1.69, 95 % CI 1.18, 2.41) and ranitidine (adjusted OR 1.37, 95 %CI 1.10, 1.70). However, no definitive exposure-response relationships between these medicines and cancer risk were observed. Conclusions: There is little evidence that commonly-prescribed medicines associated with inflammation of the pancreas are also associated with pancreatic cancer. These findings should provide reassurance to patients and prescribing clinicians.